Whitehead's Map of Victoria: revised to date with the new counties distincty coloured and alphabetical key (Printed and Published by E. Whitehead and Co., 1879)
[Inne informacje] s. 17-22.
printed and published by E. Whitehead and Co.
Keywords: Mapy drogowe; Australia; Kartografia; Wiktoria (Australia); w kartografii